Možnosti zdravljenja endometrioze - Košir-Pogačnik, Renata (Medicinski razgledi, 2009)
Endometriosis is an estrogen dependent disease that affects 5-10% of women ofreproductive age. The disease occurs most commonlyon the uterosacralligaments, in the pouch of Douglas, on the oviducts and on the ovaries. Nowadays, prevailing opinion about endometriosis is based on presumption, that endometriosis is a result of changed immune system. The treatment approach towards endometriosis can be either surgical or with medicaments.Medicamental treatment of endometriosis is focused on the hormonalalterations such as danazol, progestational drugs, gestrinone, combination of an estrogen and a progestogen and gonadotropin - relasing hormone agonists. Hormonal manipulation can only temporarily affect endometriosis, and quite dearly do es not address the underlying aetiology of the disease. The goal of conservative surgery is to remove all apparent endometriosis and restore normal anatomical relations. This approach is used with unfertile women and women seeking conception. With definitive surgery notonly all endometriosis is removed, but also the ovaries and the uterus. Theimmunological theory of etiopathogenesis of endometriosis leads to an immunological treatment approach with immunomodulators.
Keywords: Endometriosis; Bolečina; Drug Therapy; Endometrioza; ginekologija; Surgery; therapy; zdravljenje; Pain; kirurško zdravljenje